Optimization of amino acid-stabilized erythropoietin parenteral formulation: In vitro and in vivo assessment - Fayed Bahgat E.; Tawfik Abdulkader F.; Yassin Alaa Eldeen B. (Acta Pharmaceutica)
The aim of this study was to optimize the formulation of erythropoietin (EPO) using amino acids instead of human serum albumin (HSA) and to evaluate its in vivo stability in order to avoid the risk of viral contamination and antigenicity. Different EPO formulations were developed in such a way as to allow studying the effects of amino acids and surfactants on the EPO stability profile. The main techniques applied for EPO analysis were ELISA, Bradford method, and SDS gel electrophoresis. The in vivo stability was evaluated in a Balb-c mouse animal model. The results showed that the presence of surfactant was very useful in preventing the initial adsorption of EPO on the walls of vials and in minimizing protein aggregation. Amino acid combinations, glycine with glutamic acid, provided maximum stability. Formulation F4 (containing glycine, glutamic acid and Tween 20) showed minimum aggregation and degradation and in vivo activity equivalent to commercially available HSA-stabilized EPO (Eprex®).